Linking Manager Leadership To Employee Performance: The Mediating Role Of Work Discipline - Enjang Suherman; Suroso; Neni Sumarni (Universitas Dr. Soetomo, 2023)
This study examines the influence of manager leadership on employee performance through work discipline. The method used in this research is the descriptive verification method. The sample of this research is 99 employees. The sampling technique in this study uses the probability random sample method, namely random sampling or simple random sampling, where each population has the opportunity to become a sample. The analytical model used in this study is a statistical descriptive analysis model using the outer model, inner model and hypothesis test. This descriptive study shows that manager leadership is in the perfect category, work discipline is in the very high category, and employee performance is in the excellent category. While the results of the verification of manager leadership on employee work discipline have a positive and significant effect, work discipline has a positive and significant effect on employee performance, and manager leadership has a positive and significant effect on employee performance mediated by work discipline.